A New Evaluation Method for Water Blocking Performance of Coal Seam Floor: Model Construction, Case Application, and Water-Preserved Strategy. (2nd May 2022) - Gao, Baobin; Ren, Chuangnan; Song, Shaopeng
Abstract : In order to scientifically guide the water-preserved mining of the coal seam floor and make up for the shortcomings in the conventional evaluation of water blocking performance of the coal seam floor, according to the system resilience theory, the difference between the vulnerability and resilience of the coal seam floor is analyzed, and three elements and nine indicators for evaluating water resistance toughness of the coal seam floor are determined. In the evaluation process, first of all, the maximum difference normalization method is used to conduct a dimensionless analysis of quantifiable indicators to determine the importance of the corresponding indicators, and the AHP software yaahp10.1 is used to determine the weight vector of each indicator. Secondly, the single-factor membership degree is determined according to the single-factor resilience grade classification criterion and membership function and finally combined with the weight vector for fuzzy synthesis calculation and comprehensive evaluation. The model is applied to a specific project. Research has shown that in the water hazard threat area of No. 10 coal seam floor in Jiegou Coal Mine, Anhui Province, the performance of system vulnerability elements is weak, the performance of system recoverability elements is better, and the performance of system adaptability elements is extremely poor. From the perspective of the whole life cycle, determining the treatment target area, optimizing the rock formation modification and repairing materials, and enhancing the water resources carrying capacity can improve the water resistance toughness of the coal seam floor. Related conclusions verify the effectiveness of the evaluation model. Furthermore, an optimized strategy for coal seam floor water retention mining is proposed: the technology system of water-preserved mining for coal seam floor contains 3 stages and 3 detections, which provides a scientific basis for the in situ protection of high-pressure limestone water from coal seam floor.